Cambiando de rumbo. Contribución a una estrategia energética global - Öko Institut / Fundación Böll, (Revista Española de Desarrollo y Cooperación, 2023)
A global sustainable energy system must rely on energy efficiency and renewable sources of energy – this is the consensus from a variety of research and policy analysis carried out after the Rio 92 World Summit. An efficient world energy system run by renewables, thus fostering human development without compromising the global environment offers a feasible vision for the 21st century. The shift towards sustainable energy systems creates tremendous opportunities for private investments, job creation and economic development, especially in rural areas. In this sense, the Heinrich Böll Foundation asked the Öko Institute to prepare a document containing the key elements of a Global Energy Strategy, that this pages summarized.